2016
DOI: 10.1103/physrevlett.116.055501
|View full text |Cite|
|
Sign up to set email alerts
|

Carbon Honeycomb High Capacity Storage for Gaseous and Liquid Species

Abstract: We report an exceptionally stable honeycomb carbon allotrope obtained by deposition of vacuum-sublimated graphite. The allotrope structures are derived from our low temperature electron diffraction and electron microscopy data. These structures can be both periodic and random and are built exclusively from sp^{2}-bonded carbon atoms, and may be considered as three-dimensional graphene. They demonstrate high levels of physical absorption of various gases unattainable in other carbon forms such as fullerites or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
125
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(136 citation statements)
references
References 19 publications
4
125
0
Order By: Relevance
“…a) Transmission electron microscopy (TEM) images of a carbon film showing the honeycomb structure. Reproduced with permission . Copyright 2016, American Chemical Society.…”
Section: D Nanostructures For High Thermal Conductivitymentioning
confidence: 99%
See 1 more Smart Citation
“…a) Transmission electron microscopy (TEM) images of a carbon film showing the honeycomb structure. Reproduced with permission . Copyright 2016, American Chemical Society.…”
Section: D Nanostructures For High Thermal Conductivitymentioning
confidence: 99%
“…Copyright 2016, Springer Nature. 18, Reproduced with permission . Copyright 2016, American Physical Society.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, carbon honeycombs, another 3-D carbon allotrope, has been experimentally synthesized by depositing vacuumsublimated graphite [4], and immediately became a research focus [5e9]. Indeed long before the successful synthesis of carbon honeycombs, a few hypothesized structures, which were sometimes called carbon foams, had been proposed [10e17].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, experimental evidence has shown that smallest SWNTs with diameters of about 0.4 nm exist as an inner core of multiwall carbon nanotubes and can also be found in the nanosize channels of porous materials [39,40]. Moreover, Krainyukova et al [22] have recently reported a stable 3D-C by the deposition of vacuum-sublimated graphite that points out to the possibility of obtaining a (6 3 ) 3D-C structure. These experimental observations thus support a realization of the other 3D-C ALs in the near future.…”
Section: Energymentioning
confidence: 99%